P052: Breaking down the pieces: A scoping review exploring the components of image ordering interventions and trends in their outcomes in pediatric emergency medicine. (May 2019) - Gaudet, L.; Krebs, L.; Carr, M.; Kruhlak, M.; Hall, A.; Mahoney, K.; Sevcik, B.; Rowe, B.
Abstract : Introduction : Clinicians treating children in the emergency department (ED) are especially concerned with the efficacy and safety of imaging. Interventions to limit imaging have been proposed to maximize benefits and avoid risks; however, the types and effectiveness of interventions employed in pediatric EDs have not been examined in detail.Methods : Electronic databases and grey literature were systematically searched by a medical librarian. Comparative studies of ED-based interventions reporting computed tomography (CT), radiography (XR), or ultrasound (US) outcomes were included. Interventions introducing new imaging equipment or personnel to the ED, ED diversion strategies, and pre-admission protocols were excluded. At least two independent reviewers assessed each study for inclusion based on pre-defined criteria and extracted data. Disagreements were resolved through consensus. Descriptive results are reported.Results : Overall, 38 pediatric studies were included. Most (66%) interventions implemented two or more components; the most common intervention components were clinical guidelines or pathways (87%) and education or information (66%). Studies were categorized by presentation type: traumatic (n = 27); non-traumatic (n = 19), or combined 'all-comers' (n = 2). Included studies reported 62 imaging outcomes (CT = 29; XR = 20; US = 13). Among traumatic studies, 26 imaging outcomes were reported; CT was the most commonly reported outcome (CT = 15; XR = 9; US = 1). Of the CT outcomes, 33% reported significant decreases and five decreased but were either not significant or did not report significance. XR significantly decreased in 44% (4/9). In the non-traumatic studies, the most common imaging outcome remained CT (12 outcomes); 58% of which reported significant decreases. XR was the second most frequent outcome, with 63% reporting significant reductions. Combined success of the interventions to reduce CT and XR was 60%. Reported changes in ordering were less consistent in US.Conclusion : Multifaceted passive interventions have been implemented to reduce imaging in pediatric EDs. Most reported some success changing ordering practices, specifically among patients with non-trauma presentations. Future research exploring relationships between intervention content, effectiveness, and fidelity may provide insight into how to develop more effective interventions to change image ordering in the ED and guide which presentations to target.